WILLINGNESS TO PAY FOR IMPROVED SOLID WASTE DISPOSAL IN TEMA METROPOLIS - Nkansah, E.; Dafor, N.K; Essel-Gaisey, F. (UDS International Journal of Development, 2016)
The main objective of this study was to find out the willingness to pay for improved solid waste disposal in the Tema Metropolis using the Contingent Valuation Method (CVM).Â A cross-sectional survey design was used to carry out the study. A survey questionnaire was administered to respondents to draw a sample of 156 for the study. The Tobit regression was used to estimate the determinants of willingness to pay for improved solid waste disposal. The Tobit result revealed that age, educational level, number of dependants, income, size of household and distance to the refuse dump were important in explaining the willingness to pay for solid waste disposal. It is concluded that income, education level, number of dependants, household size influence the willingness to pay for sanitation improvement. We recommend that government in collaboration with waste collecting agencies should invest more resources into the provision of recycling plants that will help in dealing more efficiently and effectively with the waste disposal problem. Furthermore, the educational campaigns of the various metropolitan, municipal and district assemblies on good sanitation practices should be intensified to increase the awareness of households. The various environmental units of the district assemblies should also be well resourced to effectively enforce sanitary laws. Keywords: Willingness to pay, Improved solid waste disposal, Tema Metropolis, Contingent valuation method